Efforts to improve activities and learning outcomes ips through cooperative learning models numbered heads together - Nuriyasmiati Nuriyasmiati; Khairani Khairani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2019)
This research was based on the fact that the activity and learning results of students of grade IX.5 at SMPN 5 Bukittinggi were low. The purpose of this research was to gain information and discuss the improvement of activity and learning results of Social Study by using cooperative model type Numbered Heads Together. This research was a Classroom Action Research (CAR) with qualitative approach. There were 2 cycles in this research, each of which consisted of 4 meetings namely planning, application, observing, and reflecting procedures. The subject of this research was the students of grade IX.5 of SMPN 5 Bukittinggi which consisted of 34 students; 15 females and 19 males. The instruments used in this research were test, students’ activity observation sheet, questionnaire, interview, documentations, and field notes. The data was analyzed by using percentage technique. The result of this research showed that the application of Numbered Heads Together could improve the activity and learning result of Social Study of grade IX.5 students of SMPN 5 Bukittinggi.